Organic matter and mineral matrix of soils: modern approaches, definitions of terms and methods of study (review) - V. A. Kholodov; O. B. Rogova; M. P. Lebedeva; E. B. Varlamov; D. S. Volkov; A. R. Ziganshina; N. V. Yaroslavtseva (Бюллетень Почвенного института им. В.В. Докучаева, 2023)
Due to the complexity and heterogeneity of soil organic matter, a very wide range of methods and approaches is used to study it. This generates an excessive number of terms, definitions and indices, which makes it difficult to understand and interpret the data of different authors. The paper provides an overview of the currently most relevant methods and approaches for studying soil organic matter (SOM) and its mineral matrix. The review considers the concept of soil organic matter, its pools and fractions, the concept of soil carbon saturation. The main approaches to assessing the content, structure, and structure of pools of organic matter are described. The methods of estimation of content, structure and composition of theoretical pools of SOM are considered: biological, densimetric, granulometric, chemical and thermal fractionation. A special attention is paid to thermal methods of analysis as a promising direction for studying the non-hydrolyzable part of organic matter. It is emphasized that in the study of SOM pools, which are theoretically distinguished by behavior in time (usually by stability), about their quantity, composition and physical properties are judged by fractions, which are instrumentally determined properties of soils. Approaches are shown for studying the mineral matrix of soils and organic matter from the point of view of modern soil mineralogy and micromorphology. The influence of soil mineral composition on granulometric and chemical composition of the soils, physico-chemical absorption capacity and organo-mineral interactions is evaluated. In the description of organo-mineral components, terms and concepts of particles and structure of clay minerals – phyllosilicates – are especially considered.